(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Customer satisfaction is a commonly used term in marketing to gauge how well a company’s products and services meet or exceed customer expectations. It is measured by the number or percentage of customers whose reported experience with a company surpasses predefined satisfaction goals. To assess satisfaction, firms typically inquire whether the product or service has met or exceeded expectations. Expectations play a crucial role in customer satisfaction, as customers who have high expectations but encounter a reality that falls short are likely to be disappointed and rate their experience as unsatisfying.